Harry Potter and the chamber of secrets - Rowling, Joanne K. (Bloomsbury, 1998)
When the Chamber of Secrets is opened again at the Hogswart School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been unleashed on the school. "Surely the vilest household in children's literature since the family Roald Dahl created for Matilda. Harry himself is the perfect confused and unassuming hero." -- School Library Journal, starred review "A brilliantly imagined and beautifully written fantasy." -- Booklist